Efforts of Guidance Counseling Teachers in Handling Students: High School Level - Andra Andra; Moatti Dylan; Frances Alon (International Journal of Educational Narratives, 2023)
Background. of the guidance and counseling teacher's efforts in dealing with delinquency of class XI students at SMAN 1 Batur, Batur District, Banjarnegara Regency, in this study has an educational background that is closely related to strong character. Purpose. While development in Indonesia is carried out as a whole, which requires quality human resources, various efforts to form the nation's personality, especially in the younger generation. Method. One of the efforts to increase quality resources is through education. Results. However, every educational process, especially tackling delinquency, has obstacles and obstacles, which occur at SMAN 1 Batur, especially class XI, this research has a goal. 1) find out the efforts of the counseling teacher in dealing with student delinquency; 2) know the method used. Conclusion It was proveb by the calculation of N-gain of 0,76 with category.